2012
DOI: 10.3126/njr.v1i1.6318
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Pancreatic Lipomas: A Case Series on 64 Slice MDCT done for Different Pathologies

Abstract: Pancreatic lipomas are rare benign lesions, with only 50 cases being documented in the current literature to the best of our knowledge. We describe four cases of intrapancreatic lipomas from a single institution, all incidentally found using multi detector computed tomography within a 6-month period. Computed tomography depicted lipomas as homogeneous, nonenhancing, well-marginated lesions with a density coefficient consistent with adipose tissue. DOI: http://dx.doi.org/10.3126/njr.v1i1.6318 Nepalese Journal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The established high prevalence of pancreatic lipomas is in accordance with the observations of Stadnik et al and Dwivedi et al, who suggested that pancreatic lipomas may be more common than reported before [ 1 , 2 ]. However, that high prevalence is in clear contrast to the relatively small number of case reports in the literature, and this discrepancy needs to be explained.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The established high prevalence of pancreatic lipomas is in accordance with the observations of Stadnik et al and Dwivedi et al, who suggested that pancreatic lipomas may be more common than reported before [ 1 , 2 ]. However, that high prevalence is in clear contrast to the relatively small number of case reports in the literature, and this discrepancy needs to be explained.…”
Section: Discussionsupporting
confidence: 91%
“…Lipomatous pseudohypertrophy of the pancreas is characterized by replacement of pancreatic tissue by fat and enlargement of the parenchyma, clinically accompanied by exocrine pancreas insufficiency [6]. Like in our case series, most pancreatic lipomas are incidentally found during abdominal cross-sectional imaging [1,2,7]. Symptomatic pancreatic lipomas due to obstruction of the biliary tracts have been reported and may require surgery [5].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…They stated that the lipoma dimensions were 1.7 x 1.9 cm, 2.5 x 1.7 cm, 0.9 x 0.9 cm, 1.2 x 1.2 cm, 0.4 x 1.5 cm. Dwivedi et al (2011) found 4 pancreatic lipomas as a result of 6-month screening. They reported that the lipoma dimensions were 0.4 x 0.8 x 1.1 cm, 1.1 x 1.7 x 1.8 cm, 0.6 x 0.8 x 0.7 cm, 1.1 x 1.2 x 1.3 cm.…”
Section: Case Reportmentioning
confidence: 99%
“…analyzed 6000 CT scans and identified 5 of them as a pancreatic lipomas (0,083%). They stated that the lipoma dimensions were 1.7 x 1.9 cm, 2.5 x 1.7 cm, 0.9 x 0.9 cm, 1.2 x 1.2 cm, 0.4 x 1.5 cm Dwivedi et al (2011). found 4 pancreatic lipomas as a result of 6-month screening.…”
mentioning
confidence: 99%